Occupation-modulated language networks and its lateralization: A resting-state fMRI study of seafarers - Wu, Huijun; Peng, Deyuan; Yan, Hongjie; Yang, Yang; Xu, Min; Zeng, Weiming; Chang, Chunqi; Wang, Nizhuan (Frontiers in Human Neuroscience, 2023)
Studies have revealed that language network of Broca and Wernicke is modulated by disease, gender, aging, handedness, etc. However, how occupational factor modulates language network remains unclear. In this study, taking the professional seafarers as an example, we explored the resting-state functional connectivity (RSFC) of language network with seeds (the original and flipped of Broca and Wernicke). First, seafarers weakened RSFC of Broca with left superior/ middle frontal gyrus and left precentral gyrus, while enhanced RSFC of Wernicke with cingulate and precuneus. Further, seafarers had a less left-lateralized RSFC with left inferior frontal gyrus, while the control showed an extremely bilateral RSFC pattern in Broca and Wernicke. Moreover, seafarers displayed stronger RSFC with the left seeds of Broca and Wernicke. These findings suggest that years of working experience significantly modulates RSFC of language networks and its lateralization, providing rich insights into language networks and occupational neuroplasticity.